Discriminant value of repetitive behaviors in families with autism spectrum disorder and obsessional compulsive disorder probands. Issue 11 (19th July 2021) - Lefebvre, Aline; Cohen, Alicia; Maruani, Anna; Amsellem, Fréderique; Beggiato, Anita; Amestoy, Anouck; Moal, Myriam Ly‐Le; Umbricht, Daniel; Chatham, Christopher; Murtagh, Lorraine; Bouvard, Manuel; Leboyer, Marion; et al.
Abstract: Repetitive behaviors (RB) represent a wide spectrum of symptoms ranging from sensory‐motor stereotypies to complex cognitive rituals, frequently dichotomized as low‐ and high‐order sub‐groups of symptoms. Even though these subgroups are considered as phenomenologically distinct in autism spectrum disorder (ASD) and obsessive–compulsive disorder (OCD), brain imaging and genetic studies suggest that they have common mechanisms and pathways. This discrepancy may be explained by the frequent intellectual disability reported in ASD, which blurs the RB expressivity. Given the high heritability of RB, that is, the diversity of symptoms expressed in the relatives are dependent on those expressed in their probands, we hypothesize that if RB expressed in ASD or OCD are two distinct entities, then the RB expressed in relatives will also reflect these two dimensions. We thus conduct a linear discriminant analysis on RB in both the relatives of probands with ASD and OCD and subjects from the general population ( n = 1023). The discriminant analysis results in a classification of 81.1% of the controls ( p < 10 −4 ), but poorly differentiated the ASD and OCD relatives (≈46%). The stepwise analysis reveals that five symptoms attributed to high‐order RB and two related to low‐order RB (including hypersensitivity) are the most discriminant. Our results support the idea that the difference of RB patterns in the relatives is mild compared with the distribution of symptoms in controls. Our findings reinforce the evidence of a common biological pattern of RB both in ASD and OCD but with minor differences, specific to each of these two neuro‐developmental disorders. Lay summary: Repetitive behaviors (RB), a key symptom in the classification of both OCD and ASD, are phenomenologically considered as distinct in the two disorders, which is in contrast with brain imaging studies describing a common neural circuit. Intellectual disability, which is frequently associated with ASD, makes RB in ASD more difficult to understand as it affects the expression of the RB symptoms. To avoid this bias, we propose to consider the familial aggregation in ASD and OCD by exploring RB in the first‐degree relatives of ASD and OCD. Our results highlight the existence of RB expressed in relatives compared to the general population, with a common pattern of symptoms in relatives of both ASD and OCD but also minor differences, specific to each of these two neuro‐developmental disorders.